Pengelolaan Rumah Singgah Sebagai Ruang Baca Perpustakaan Umum Kota Solok - Sabda, Sabda; Ardoni, Ardoni; Sabda Sabda (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paperaims to describe the Shelter Home Management provided Solok City Public Library. Based on theresults of the survey and the analysis found that the Shelter Home Management Solok City Public Library began with the planning of activities organized by Solok City Public Library. The nextplanis organizedin a coordinated manner by the employee or staff assigned tomanage thes helter. Operational activitiesin thes helter directly supervised by the Public Library of Solok and must submita reporton the application to the head of the library budget. From the report managers helters will receive direction from the head of the library if necessary. Of these findings should be expected Solok City Public Library include eshelt ermanagers in creatingan action plan that will be implemented by the halfway house. In operations hould need additional staff fing shelters because of the density of the activities to becarried out by the halfway house. Keywords: library; information; shelter home